(untitled) (International Journal of Pharmaceutical Sciences and Drug Research, 2019)
Three medicinal plants with recognized anti-inflammatory potential, identified as “erva de São João“ (Ageratum conyzoides), “Tanchagem“ (Plantago major) and “ Bardana“ (Arctium lappa L.) were obtained from a medicinal herbs company located in Teófilo Otoni city (Minas Gerais State, Brazil). The dry plant material obtained in packages was submitted to the chemical procedures to prepare the crude extracts by maceration according to the Brazilian pharmacopoeia legislation. After extraction, the samples were subjected to 1H NMR, TLC and Capillary Electrophoresis analysis by co-injection of authentic patterns of phenolic acids and flavonoids to identify the major compounds and classes of secondary metabolites present in each material and then their chemical and biological potential was assessed by DPPH free radical inhibition assay and antimicrobial against E. coli. The results obtained allow us to conclude that the phytopreparation was effective in the extraction of compounds with antioxidant potential and the three species presented a high concentration of flavonoids and other phenolics that is compatible with the chemosystematic data. The screening obtained by 1H NMR spectroscopy, TLC and Capillary Electrophoresis with ultraviolet detection analysis provided us a qualitative profile of the phytochemicals present in each material. None of the extracts were active against Escherichia coli by antibacterial disk diffusion assay at concentration of 1 mg/ml.